2002
DOI: 10.1021/ol0260573
|View full text |Cite
|
Sign up to set email alerts
|

New Polyhydroxylated Pyrrolidines Derived from Enantiopure 3,6-Dihydro-2H-1,2-oxazines

Abstract: [reaction: see text] Diastereoselective hydroborations of enantiopure 3,6-dihydro-2H-1,2-oxazines led to dihydroxy-substituted 1,2-oxazines. Samarium diiodide-induced N-O bond cleavage generated 1,4-amino alcohols which were recyclized to polyhydroxylated pyrrolidines which are potential glycosidase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 16 publications
(7 reference statements)
3
28
0
1
Order By: Relevance
“…In previous experiments with 1,2-oxazines, stereoselective hydroboration has proved to be a very useful method to functionalize the enol ether double bond. [3] Application of this procedure to bicyclic 1,2-oxazine 7 furnished the expected hydroxy-substituted compound 9 in excellent diastereoselectivity (dr Ͼ 95:5) and good yield for the crude product (Scheme 5). However, after chromatography pure 9 was isolated in only 40% yield.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous experiments with 1,2-oxazines, stereoselective hydroboration has proved to be a very useful method to functionalize the enol ether double bond. [3] Application of this procedure to bicyclic 1,2-oxazine 7 furnished the expected hydroxy-substituted compound 9 in excellent diastereoselectivity (dr Ͼ 95:5) and good yield for the crude product (Scheme 5). However, after chromatography pure 9 was isolated in only 40% yield.…”
Section: Resultsmentioning
confidence: 98%
“…The authors also demonstrated that these 1,2-oxazines are valuable intermediates for the synthesis of enantiopure furan and pyran derivatives, [2] amino alcohols [3,4] and pyrrolidines. [3,4] …”
Section: Introductionmentioning
confidence: 99%
“…[18] On the other hand, direct cyclodehydration strategies are more straightforward, but come at the expense of costly reagents and scale-up issues. [19] One simple and elegant solution to this problem entails the chlorination of the alcohol with SOCl 2 followed by ring closure. While conceptually simple, the successful implementation of this strategy has been problematic because of the competition between N-and O-sulfinylation followed by side reactions, which ultimately lead to low yields of the desired cyclic amines.…”
Section: Proton-mediated Chemoselectivitymentioning
confidence: 99%
“…Early work by Knochel and co-workers demonstrated that alkyl zinc reagents prepared by the reaction of zinc dust with an appropriate organohalide were not destroyed in the presence of acidic protons (pK a [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. [157,158] In 2006, Uchiyama et al reported that the halogen-metal exchange of a haloarenes bearing acidic hydrogen atoms could be accomplished with tBu 4 ZnLi 2 without quenching the reagent or the resulting aryl zincate.…”
Section: Selecting Between Carbon-carbon Coupling Reactionsmentioning
confidence: 99%
“…Zu erwähnen sind hier vor allem mehrfach hydroxylierte Pyrrolidinderivate, stereodefinierte Aminopolyole und substituierte Tetrahydrofuranderivate. [2] Alle Produkte sind wegen ihrer möglichen biologischen Aktivität, z. B. als Glycosidaseinhibitoren, interessant.…”
unclassified